The political significance of Winnie-Madikazela Mandela's position in the African National Congress - Motseta, Sello (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
Winnie Mandela has endured so many scandals over the last ten years that she has acquired a reputation for being untouchable. It is therefore ironic that there are those who feel that "the ANC want to act against Winnie not because of her human rights record, but for her outspoken criticism of the government's inability to deliver houses, thwart crime and testing our feelings on the death penalty." This assessment is instructive because in the "... turbulent years of the 1980s, she was a hero, a living martyr to the black liberation cause and despite the discomforts inflicted on her by her perpetrators, she revelled in the role" (Sparks, 1994:15). But Winnie Madikazela-Mandela, who was a Deputy Minister before being dismissed and who has had to appear before the TRC because of allegations that she was responsible for the death of teenage activist Stompie Seipei, has nevertheless been able to make a political comeback. The thesis therefore sets out to examine the rationale behind the State President's (he did not hold this title then) decision to take a considerable risk in standing by Winnie Madikazela-Mandela (they were at the time married) during her trial on charges of kidnapping in 1991. Even after her conviction, Mandela wrote that "as far as I was concerned, verdict or no verdict, her innocence was not in doubt." This unstinting loyalty was replicated elsewhere. Commenting on her acquittal on the assault charges, ANC Youth League President, Peter Mokaba, said: "What was taken away from her as a result of these false allegations must now be given back". He described the Appellate Division decision as "a political sentence" saying: "It has nothing to do with whether she was guilty or not."3 The ANC has established a practice of accommodating dissidents within its structures and has survived complex challenges during its years in exile by doing so. But political commentators are now asking whether the political cost will prove to be too great.
Keywords: African National Congress; Mandela, Winnie; South Africa -- Politics and government -- 1994-